The 12th Conference of the International Sports Engineering Association 2018
DOI: 10.3390/proceedings2060294
|View full text |Cite
|
Sign up to set email alerts
|

Utilising GPS Data to Quantify Torso Range of Motion in Field Hockey Athletes

Abstract: Global Positioning System (GPS) along with micro-electrical mechanical system (MEMS), technology is now commonplace in today's sporting environment. Little has been published utilising this combination of technologies to quantify the postures of athletes during match-play. This paper presents the results of a preliminary investigation into developing a methodology that allows practitioners to use the technology readily available to them to quantify the postural demands of field hockey players during match-play. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, a novel approach was conducted by analyzing the effect that different contextual variables (e.g., playing position, match half, and match day) had on the postural demands. Although the only investigations that have analyzed the trunk kinematics have been carried out in field hockey players, our study with soccer players tried to improve the applied methodology since these investigations presented two major limitations: the sample of matches (6 matches and 1 match, respectively) [ 10 , 11 ] and the use of different instruments for data collection within the same investigation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a novel approach was conducted by analyzing the effect that different contextual variables (e.g., playing position, match half, and match day) had on the postural demands. Although the only investigations that have analyzed the trunk kinematics have been carried out in field hockey players, our study with soccer players tried to improve the applied methodology since these investigations presented two major limitations: the sample of matches (6 matches and 1 match, respectively) [ 10 , 11 ] and the use of different instruments for data collection within the same investigation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, elite soccer matches are characterized by fast paces of play which require high demands of perceptual-motor skills of the players (e.g., continuous interaction with teammates in a specific space and time to dribble the ball while considering the opposition players) [ 7 , 8 , 9 ]. In consequence, recent investigations on other team sports (e.g., field hockey) have suggested that a better understanding of the postural demands of the players is necessary [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of the tactical connection between MF and the rest of the playing positions in addition to their role as game organizers (e.g., passing the ball and linking the sectors of the team) [ 33 ], these results may be explained by the fact that this position requires an upright posture at greater speeds in order to perform in their field of regard [ 4 , 5 ]. From a practical perspective, this is one of the reasons why previous researchers suggested that it is important to understand the postural demands of the players during the sport-specific skills [ 4 , 21 , 34 ]. For example, if a player tends to increase trunk flexion when sprinting, this may lead to the downward orientation of the head and restrict the ability to perform in the field of regard [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the gold standard instruments for this aim are the motion capture systems, these are limited to laboratory settings [ 19 , 20 ]. In recent years, wearable inertial measurement units have been considered as alternative instruments for motion capture, since these may give insight into how soccer players use their trunk to perform the sport-specific skills in match play [ 4 , 21 ].…”
Section: Introductionmentioning
confidence: 99%